Role of expert coaches in development of top-level athlete's careers in individual and team sports - Trninic, V.; Papic, V.; Trninic, M. (Acta Kinesiologica, 2009)
Coach's expert knowledge and experience, as well as scientific acquisitions confirm the importance of the role of expert coaches in the development of careers of potential top-level athletes in individual and team sports. It is very important for the expert coach to know how to make and insist on demands that are prime in stimulating the development of athlete's potential. From the motor learning and training theory's point of view, athlete's development is a continuous process. The role of expert coaches in athlete's development in individual and team sports primarily includes stimulating the development of athlete's personality and his understanding of a particular sport, skill development, upgrading the level and the number of motor programmes, and encouraging the development of selective decision-making and decreasing the reaction period. The specificity and individualisation of the training-competition process enables the athlete to achieve optimal development of genetic potential and total efficacy in a particular sport. A top-level teacher and/or coach encourage continuity in learning and in perfectioning technical-tactical knowledge and skills, development of competitive experience, and psychosocial development of athlete's personality as a discontinuous process. Empirical research confirms that athlete's career is determined by genetic factors, the process of sports preparation and also by lifestyle in all periods of his development.